Evaluation on quality consistency of Ganoderma lucidum dietary supplements collected in the United States - Ding-Tao Wu (Nature Portfolio, 2017)
Abstract Ganoderma lucidum is a well-known medicinal mushroom. At present, numerous G. lucidum products have emerged in the form of dietary supplements in the United States due to its various benefits. However, the quality consistency of these products based on their label ingredients has seldom been evaluated due to the lack of a suitable toolkit. In this study, 19 batches of products of G. lucidum (Red Reishi, Reishi), herbal/mushroom supplements purchased in the United States, were evaluated based on their bioactive components including triterpenes and polysaccharides by using chromatographic methods and saccharide mapping. The results showed that the measured ingredients of only 5 tested samples (26.3%) were in accordance with their labels, which suggested the quality consistency of G. lucidum dietary supplements in the U.S. market was poor, which should be carefully investigated.